Virtual reality simulation system for water supply and distribution network. (21st December 2012) - Wu, Wenyan; Gao, Jinliang; Chang, Kui
One of the challenges of Virtual Reality (VR) technology is implementing its effective integration with application models to provide feasible information in real time. This paper will investigate VR simulation systems in Water Distribution Networks (WDN). A framework of a VR simulation system for WDN was proposed and a prototype was developed to provide an intuitive user interface offering real–time simulation and interaction through multi–sensory channels. This enables data processing, visualisation, scene roaming, hydraulic and water quality calculation and network analysis. The hydraulic and water quality models are combined into the VR simulation system; dynamic hydraulic and water quality information is expressed visually and managed interactively in the three dimensional virtual environment. The proposed VR simulation framework and developed system were evaluated in a case study which demonstrated its effectiveness as a tool to enhance understanding and operational efficiency in the WDN.